MOSFET Variable Bench Power Supply / Janatul Naim Mustafa and Siti Nursyida Azuddin - Mustafa, Janatul Naim; Azuddin, Siti Nursyida Azuddin (2005)
MOSFET Variable Bench Power Supply is an unusual and highly efficient design developed from,a previous electronic project. It can supply 0 to 25 volts at up to 2.5 volts. The benefit of this project is it uses a high output voltage of 0 to 25 volts, and a maximum output current capability of 2.5 amps far better than the more usual 12 volts and 1 amp supplies. An outpilt voltage can be reduced right down to zero and a current limit control, which allows the maximum output current to be set anywhere between zero and maximum. Two-panel meters monitor output Voltage and Current to make it easy to see exactly what is happening in a circuit. Ripple and noise in the output are very low, and mains voltage fluctuations are very small. This circuit can be operated by the first and most important change by added which dramatically reduces the power lost in the MOSFET to the circuit. This is achieved by a low frequency switching pre-regulator, which reduces the voltage across the main smoothing capacitor so that it is never more than 5 volts above the output voltage setting. This type of pre-regulator is called a hacking pre-regulator because it follows the output voltage at a fixed distance.